Extending the reach of personal area networks by transporting Bluetooth communications over IP networks - Mackie, David Sean (Rhodes University, Faculty of Science, Department of Computer Science, 2007)
This thesis presents an investigation of how to extend the reach of a Bluetooth personal area network by introducing the concept of Bluetooth Hotspots. Currently two Bluetooth devices cannot communicate with each other unless they are within radio range, since Bluetooth is designed as a cable-replacement technology for wireless communications over short ranges. An investigation was done into the feasibility of creating Bluetooth hotspots that allow distant Bluetooth devices to communicate with each other by transporting their communications between these hotspots via an alternative network infrastructure such as an IP network. Two approaches were investigated, masquerading of remote devices by the local hotspot to allow seamless communications and proxying services on remote devices by providing them on a local hotspot using a distributed service discovery database. The latter approach was used to develop applications capable of transporting Bluetooth's RFCOMM and L2CAP protocols. Quantitative tests were performed to establish the throughput performance and latency of these transport applications. Furthermore, a number of selected Bluetooth services were tested which lead us to conclude that most data-based protocols can be transported by the system.
Keywords: Bluetooth technology; Communication -- Technological innovations; Communication -- Network analysis; TCP/IP (Computer network protocol); Computer networks; Computer network protocols; Wireless communication systems